Estudos comparativos da composição proteica e dos efeitos citotóxico, oxidante, antioxidante e coagulante causados pelas peçonhas brutas de Bothrops jararacussu e Bothrops moojeni - Paixão Júnior, Otacílio Benício da (2017)
Snakebite or snakebite is the chart of poisoning from the inoculation of toxins through the snake inoculation apparatus. The objective of this study was to evaluate and in vitro the cytotoxic, oxidative and homeostasis effects (on erythrocytes, hemoglobins and human plasma, respectively) caused by the presence of the crude venoms of Bothrops jararacussu and Bothrops moojeni snakes. The protein profile of each venom was characterized by reverse phase chromatography and SDS-PAGE. The venom compositions of both species showed similar protein profiles. The amounts of the crude venoms from B. jararacussu and B. moojeni induced significant indirect hemolysis in the presence of fatty acid and fatty acid plus calcium chloride. The crude venom of B. jararacussu presented a higher cytotoxic potential. The venoms of B. jararacussu and B. moojeni, showed no anti-hemolytic effect. The venom of B. jararacussu presented a haemagglutinating effect in the analyzed amounts of 100 and 1000μg and did not present an oxidizing effect. The B. moojeni venom presented an oxidizing effect only in the amount of 1000μg. Venoms of both species showed no anti-oxidant effect. The crude venom of B. moojeni had a higher coagulant potential compared to B. jararacussu venom and all plasma clots formed were turbid, rigid and stable. The clot formation time was inversely proportional to the amount of venom evaluated. Therefore, the information obtained from the comparisons of the biological effects caused by the venoms, showed that B. jararacussu showed indirect hemolytic activity, hemagglutinating and coagulant, and B. moojeni presented indirect hemolytic activity, oxidant and coagulant.